Ser agente comunitário de saúde: motivação e significado - Peres, Cássia Regina Fernandes Biffe; Caldas Junior, Antonio Luiz [UNESP]; Silva, Roseli Ferreira da; Marin, Maria José Sanches (My University, 2010)
This study aims at characterizing the profile of the Community Health Agent (in Portuguese ACS) working in Health Centers at the municipality of Marilia-SP. It intends also to analyze the motivations and meanings of being an ACS. The quantitative data were studied descriptively whereas the qualitative results were summarized by content analysis. ACSs were predominantly of the female sex and were in average 32. 5 years old. Most of them had finished high school and had been working as Community Health Agents for an average 27 month. Unemployment, the search for a different work area and the desire to help others were pointed out as reasons for becoming an ACS. For them being an ACS means to develop links with the community, to be able to talk, to help, to guide and to encourage their autonomy as well as to offer assistance to the community. In conclusion, it is necessary to better define and improve the ACS’s responsibilities.

El presente estudio propone caracterizar el perfil de los Agentes Comunitarios de Salud (ACS) de las unidades de atención básica a la salud del municipio de Marília-SP y analizar los motivos y el significado de ser ACS. Los datos cuantitativos se enfocaron de forma descriptiva, por medio del análisis univariado. En el análisis de datos cualitativos se empleó el referente de análisis del contenido. Predominaban las mujeres con edad promedio de 32,5 años, la mayoría con enseñanza secundaria que trabajaba en esa tarea durante un promedio de 27 meses. El desempleo, la búsqueda de otro campo de trabajo y el anhelo de ayudar el prójimo constituían los motivos que las impulsaban a ser ACS. En cuanto al significado se constato la interlocución y el vínculo, la posibilidad de ayuda, la orientación y el estímulo a la autonomía, además de acciones asistencialistas. Se concluye que habría que definir y perfeccionar las atribuciones de los ACS.

Neste estudo, propõe-se caracterizar o perfil dos agentes comunitários de saúde (ACSs) das unidades de atenção básica à saúde do município de Marília-SP e analisar os motivos e o significado de ser ACS. Os dados quantitativos foram abordados de forma descritiva e para a análise dos dados qualitativos foi utilizado o referencial de análise de conteúdo. Houve predomínio de mulheres; a média de idade foi de 32,5 anos; a maioria tem ensino médio completo e atua na função, em média, por 27 meses. O desemprego, a busca de outra área para atuação e o desejo de ajudar o outro foram os motivos de se tornarem ACSs. Quanto ao significado, constatou-se a interlocução e o vínculo, a possibilidade de ajuda, a orientação e o estímulo à autonomia, além de ações assistencialistas. Conclui-se que há necessidade de que as atribuições do ACS sejam definidas e aprimoradas.
Being a community health agent: motivation and meaning
Ser agente comunitario de salud: motivación y significado
Keywords: Family Health Program; Community healthcare assistant; Public health; Programa Salud de la Familia; Auxiliares de salud comunitaria; Salud pública; Programa Saúde da Família; Auxiliares de saúde comunitária; Saúde pública